Selenium-Mediated Heavy Metals and Pesticide Toxicity Protection: Biochemical, Histopathological, and Molecular Studies in Labeo rohita - Singh, Anupama; Kumari, Shilpa; Verma, Rajesh (American Journal of Biodiversity, 2026)
Combined exposure of pollutants through industrial release and agricultural runoffs is currently threatening freshwater ecosystems. The oxidative stress of heavy metals like cadmium and organophosphate pesticides like malathion disrupts the homeostasis of the cells and poses a threat to the ecology and aquaculture. The current article examined the protective effect of selenium on combined toxicity of cadmium malathion in freshwater carp Labeo rohita through a combined biochemical, histopathological and molecular methodology. The juvenile fish were exposed to sublethal concentrations of toxicants in 21 days with or without dietary supplementation of selenium. The activities of antioxidant enzymes (SOD, CAT, GPx), the decreased glutathione (GSH), lipid peroxidation (MDA), tissue histology, and expression of stress-related gene (gpx, sod, hsp70) were examined. The existence of toxicants strongly amplified lipid peroxidation (approximately 62%) and inhibited antioxidant enzymes by 3845, which indicated the existence of severe oxidative imbalance. Histopathology showed hepatocellular necrosis, degeneration of renal tubules and gill epithelium damage. It was demonstrated by molecular evidence that stress caused the overexpression of hsp70 and the dysregulation of antioxidant genes. The major replacement of enzymatic defenses was selenium supplementation (48-55% recovery), the MDA levels decreased by approximately 40%, and GSH levels were raised to near-control levels. Tissue structure was preserved and cellular stability increased in terms of gene expression patterns. Functional protection was also exhibited by survival rates in selenium-treated groups. These results support selenium as a good micronutrient modulator that can reverse the oxidative stress of pollutants at various biological levels. The importance of selenium in the preservation of redox homeostasis, organ integrity, and stress-responsive genes. Selenium supplementation when properly calculated can thus be a potential solution to improve the resilience of aquaculture in freshwater environments with contamination. The findings are included in ecotoxicology risk assessment and are applied in the micronutrient-based interventions as a sustainable fish health management.